INFLUENCE OF REMELTING ON ALUMINUM ALUMINUM RAIN - Aris Budiyono; Jamasri Jamasri (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The purpose of this research is to observe the effect of remelting on fatigue crack growth rates of the aluminum alloys. The material used in this research was selected aluminum scraps. The material was melt and cast at temperature of 745°C in the metal molding, then was made specimen according to ASTM E. 647. The remelting was done three times at the same condition. The fatigue crack growth rate testing was performed in a room temperature condition with a constant load amplitude and the load ratio was maintained to be 0,3.The experiment result show that remelting can increase fatigue crack growth rates whichwas shown by increasing ofn exponential values (I